2016
DOI: 10.1108/pijpsm-10-2015-0120
|View full text |Cite
|
Sign up to set email alerts
|

Does discipline fairness matter for the police code of silence? Answers from the US supervisors and line officers

Abstract: Purpose -Following the theoretical model of reporting and disciplinary fairness developed by Kutnjak Ivković and Klockars (1998), the purpose of this paper is to use a survey of US police officers to explore empirically the contours of the code of silence and the potential relation between the code and perceptions of disciplinary fairness. Design/methodology/approach -In 2013-2014, a police integrity survey was used to measure the contours of police integrity among 604 police officers from 11 police agencies l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The paramilitary training model and construction of masculinity may also influence how some recruits, especially women, lesbian, gay, bisexual, and transexual officers, perceive the motivations of those who engage in behavioral corrections. Heterogeneity in cognitive schemas of fairness may help explain some of the inconsistencies in the literature (see Kutnjak Ivkovi c et al, 2016).…”
Section: Organizational Justicementioning
confidence: 99%
“…The paramilitary training model and construction of masculinity may also influence how some recruits, especially women, lesbian, gay, bisexual, and transexual officers, perceive the motivations of those who engage in behavioral corrections. Heterogeneity in cognitive schemas of fairness may help explain some of the inconsistencies in the literature (see Kutnjak Ivkovi c et al, 2016).…”
Section: Organizational Justicementioning
confidence: 99%
“…Few studies examine the intersectional nature of organizational, environmental, and individual factors and how each shape police integrity. In fact, across the dozens of studies on police integrity, only a small sample examine these factors through a more nuanced analytical approach (see Ivković, 2012; Ivković, Mraović, & Borovec, 2016b; Ivković, Peacock, & Haberfeld, 2016; Ivković & Sauerman, 2016; Kane & White, 2009; Lobnikar et al, 2016; Pagon, Lobnikar, & Anelj, 2004; Torstensson-Levander & Ekenvall, 2003; Vallmüür, 2016; Wolfe & Piquero, 2011). What follows is a brief overview of the state of research concerning the individual, organizational, and environmental factors.…”
Section: Determinants Of Police Integrity: a Literature Reviewmentioning
confidence: 99%
“…This assessment of the state of research is particularly salient within studies documenting the state of integrity within police agencies and increasingly so among those studies replicating the integrity scale created by Klockars and his colleagues (2000). In fact, much of this body of research has provided tremendous insight into observed differences across organizational ranks (Ivković, 2012; Ivković, Peacock, & Haberfeld, 2016; Lim & Sloan, 2016), although absent from these studies were an emphasis on the salient individual and contextual factors associated with different decisions. For instance, officers’ age, marital status, community assignment, and agency location (regional difference) are factors that have been rarely examined about their potential influence on police integrity, as reflected by such outcome measures as officers’ evaluation of misconduct seriousness and their adherence to the code of silence.…”
Section: Introductionmentioning
confidence: 99%
“…Other research suggests that the code of silence is somewhat conditional on the seriousness of the behavior and perceptions of fairness of discipline. More-serious misconduct is less likely to be kept secret while overly harsh punishments increase the likelihood of secrecy, and these patterns are similar across supervisors and nonsupervisors (Ivković, Peacock, and Haberfeld, 2016). To deal with the street environment, officers might be suspicious of most citizens and feel that it is important to "maintain the edge" over citizens in interactions or to establish control at the beginning of encounters.…”
Section: Policing-specific Cultural Norms and Themesmentioning
confidence: 99%
“…Additionally, interviewees had concerns over the use of force, shootings committed by deputies, and a code of silence as potential ways to enhance status within the group. Instead of relying only on increasing punishment to resolve these issues, which can backfire (Ivković, Peacock, and Haberfeld, 2016), a focus on peer intervention draws from the idea that prevention is the best medicine and emphasizes that anyone can intervene with anyone else to protect their career, health, or safety. There is likely substantial distance in LASD between those who ostracize and those who are ostracized, but our interview and survey findings suggest that there is a large middle ground of people who are respected and could also recognize the need to intervene.…”
Section: Develop a Peer Intervention Program To Help Personnel Interv...mentioning
confidence: 99%